SPARC Promotes Cathepsin B-Mediated Melanoma Invasiveness through a Collagen I/α2β1 Integrin Axis - Girotti, María R.; Fernández, Marisol; López, Juan A.; Camafeita, Emilio; Fernández, Elmer A.; Albar, Juan P.; Benedetti, Lorena G.; Valacco, María P.; Brekken, Rolf A.; Podhajcer, Osvaldo L.; Llera, Andrea S. (Journal of investigative dermatology, 2011)
In melanoma, the extracellular protein SPARC (secreted protein acidic and rich in cysteine) is related to tumor progression. Some of the evidence that links SPARC to melanoma progression indicates that SPARC may be involved in the acquisition of mesenchymal traits that favor metastatic dissemination. However, no molecular pathways that link extracellular SPARC to a mesenchymal phenotype have been described. In this study, global protein expression analysis of the melanoma secretome following enforced downregulation of SPARC expression led us to elucidate a new molecular mechanism by which SPARC promotes cathepsin B-mediated melanoma invasiveness using collagen I and α2β1 integrins as mediators. Interestingly, we also found that the transforming growth factor (TGF)-β1 contribution to cathepsin B-mediated invasion is highly SPARC dependent. In addition, induction of the E-cadherin to N-cadherin switch by SPARC enabled melanoma cells to transmigrate across an endothelial layer through a mechanism independent to that of enhancing invasion. Finally, SPARC also enhanced the extracellular expression of other proteins involved in epithelial–mesenchymal transformation, such as family with sequence similarity 3, member C/interleukin-like EMT-inducer. Our findings demonstrate a previously unreported molecular pathway for SPARC activity on invasion and support an active role of SPARC in the mesenchymal transformation that contributes to melanoma dissemination.